Emotional exhaustion and organizational commitment: Primary school teachers’ perspective - Mozes M. Wullur; Basilius Redan Werang (International Journal of Evaluation and Research in Education (IJERE), 2020)
Teaching is a noble profession to educate the youth of nations facing today’s global challenges. Teaching, at the same time, has become a highly challenging profession and occasionally a draining work, especially for those who are working in the remote areas. A high-level of teacher absenteeism in the primary schools of Southern Papua has blown some societal alarm for conducting studies focusing on emotional exhaustion as a latent predictor for low-performance. This study attempted to describe the eventual correlation between the emotional exhaustion and organizational commitment of teachers working in the primary schools of Merauke, Indonesia. A survey approach was employed to collect data from a total of 243 primary school teachers in Merauke, Papua, Indonesia. Data were examined statistically by employing Pearson’s correlation model. Results of analysis showed that the emotional exhaustion and commitment of primary school teachers in Merauke, Indonesia, are significantly negatively correlated. This result may be useful for the teachers to benefit from the information of how they may interact with all the school elements and the extent to which these emotions directly affect their organizational commitment. The result may also be advisable for the school leaders to take some tactical efforts of securing teachers’ emotion to promote a high-level of teachers’ organizational commitment and, in turn, improving students’ capabilities in reading, writing, and arithmetics.